Implementasi Teori dan Psikologi Belajar dalam Pengembangan Keterampilan Sosial-Emosional Anak di Madrasah Ibtidaiyah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Social-emotional skills are a crucial aspect of child development that significantly influence learning success and character formation. Madrasah Ibtidaiyah (MI), as an Islamic elementary education institution, plays a strategic role in developing these skills through well-planned and meaningful learning processes. This article aims to examine the implementation of learning theories and educational psychology in the development of children’s social-emotional skills in Madrasah Ibtidaiyah. This study employs a qualitative approach using a literature review method by analyzing various sources, including books, scientific journals, and relevant documents discussing learning theories, child development psychology, and Islamic basic education. The findings indicate that behaviorist, cognitive, social, and humanistic theories contribute significantly to the development of children’s social-emotional skills when implemented integratively in MI learning practices. Teachers play a vital role in creating a learning environment that supports social interaction, emotional regulation, empathy, and students’ religious attitudes in a sustainable, contextual, and holistic character-oriented manner.